Multisensory warning signals: when spatial correspondence matters. - Ho, C; Santangelo, V; Spence, C (2009)
We report a study designed to investigate the effectiveness of task-irrelevant unimodal and bimodal audiotactile stimuli in capturing a person's spatial attention away from a highly perceptually demanding central rapid serial visual presentation (RSVP) task. In "Experiment 1", participants made speeded elevation discrimination responses to peripheral visual targets following the presentation of auditory stimuli that were either presented alone or else were paired with centrally presented tactile stimuli. The results showed that the unimodal auditory stimuli only captured spatial attention when participants were not performing the RSVP task, while the bimodal audiotactile stimuli did not result in any performance change in any of the conditions. In "Experiment 2", spatial auditory stimuli were either presented alone or else were paired with a tactile stimulus presented from the same direction. In contrast to the results of "Experiment 1", the bimodal audiotactile stimuli were especially effective in capturing participants' spatial attention from the concurrent RSVP task. These results therefore provide support for the claim that auditory and tactile stimuli should be presented from the same direction if they are to capture attention effectively. Implications for multisensory warning signal design are discussed.